Persuasion for Criticism in the Architecture - Al-Majidi, Basim Hasan Hashim; Al-Hassani, Ahmed Abed Jalowb (Iraqi Journal of Architecture and Planning, 2017)
The Critique is a tool for the development of architectural production , And when that criticism in architecture depends on the parties : (Critic , Receiver , and Output ), And there is a dialogue going on between the critic and the receiver , The process depends on the acceptance or refusal, Therefore it is necessary to put a tool for Persuasion the receiver , This tool practiced by the critic to be able to Persuasion the recipient to accept the views put forward , So the process of persuasion in the critique consisting of several stimuli to criticism in general , Some of them give positive results and the other negative. The objective of the research to identify the methods of persuasion in Critique academic and sort of know any more possible ways to create a constructive criticism of the party during the second response (Receiver) to the critic, To be the research problem (There is a knowledge gap on how to convince the architectural critic of the designer in Actual Architectural Academy), The main draw of the vocabulary part of the theoretical research of the concepts related to research and previous studies, And then conducted the practical application of academic projects on one final study phase, And then go out the results and then conclusions, which belongs to The researcher found that the criticism persuade process is done through Analysis ,Technology means ,negotiation and attractions of the designer with many ways and skills to be enjoyed by architectural critic.